Ethics and Undergraduate Research in the Study of Religion: Place‐Based Pedagogy and Reciprocal Research Relations. (October 2016) - Prideaux, Mel
Abstract: In the undergraduate religious studies classroom at the University of Leeds students are introduced to the complexity of religion in locality. One of the most engaging ways to do this is through a place‐based pedagogy utilizing independent fieldwork as part of the learning process. However, undergraduates, like seasoned researchers, must learn to balance and understand the way insider representations influence academic interpretations, and the way their academic interpretations and representations can lead to change in the community being studied. Place‐based pedagogy has, therefore, an important ethical dimension that is not accounted for in the existing literature. Engaging with reciprocal research relations as a way to navigate this terrain introduces students to the human impacts of their research and develops their self‐awareness as researchers and religion specialists. This paper will draw on the Leeds experience to build an understanding of the interaction between place‐based pedagogy and reciprocal research relations which informs both teaching and research in the study of religion, and extends the existing discourse on the ethical dimensions of undergraduate research.